Materials with ferro-antiferroelectric phase transition intented for energy accumulated and converting devices - Ishchuk, V.M.; Spiridonov, N.A. (Functional Materials, 2004)
Considered are the results of development of materials for energy accumulating and converting devices. Requirements to such materials are formulated. Investigated is one of the directions for raising their efficiency which implies increase of electric strength. Рассмотрены результаты разработки материалов для энергоаккумулирующих и энергопреобразующих устройств. Сформулированы требования к таким материалам. Исследовано одно из направлений повышения их эффективности, включающее повышение диэлектрической прочности. Розглянуто результати розробки матерiалiв для енергоакумулюючих та енергопере-творюючих пристроїв. Сформульовано вимоги до таких матерiалiв. Досліджєно один із шляхів підвищення їх ефективності, який включає підвищення діелектричної міцності.